2020
DOI: 10.1111/poms.13231
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Operations Management Research: from Managing Flows to Building Capabilities

Abstract: T his forum study examines the past and the future of Operations Management (OM) research. First, we investigate the evolution of OM research from 1997 to 2018 by using machine learning tools to analyze all OM papers published in five journals (JOM, MS, M&SOM, POM, and OR), and find that the number of information/financial flow-focused OM research papers has increased steadily over the years. Second, we present three research topics motivated by the US-China trade war and the Covid-19 pandemic, and postulate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 16 publications
3
59
0
Order By: Relevance
“…A significant contribution has been observed in respect to SCR and the application of AI. It was also reported that industry 4.0 technologies can facilitate risk mitigation ability to the firms to continue their operations during disruptions (Zhang et al 2020 ). Shih ( 2020 ) supported this condition of current pandemic, where the unavailability of human labour is the most critical issue which potentially harms the operations of the supply chain.…”
Section: Discussion and Proposed Research Modelmentioning
confidence: 99%
“…A significant contribution has been observed in respect to SCR and the application of AI. It was also reported that industry 4.0 technologies can facilitate risk mitigation ability to the firms to continue their operations during disruptions (Zhang et al 2020 ). Shih ( 2020 ) supported this condition of current pandemic, where the unavailability of human labour is the most critical issue which potentially harms the operations of the supply chain.…”
Section: Discussion and Proposed Research Modelmentioning
confidence: 99%
“…"Disaster management" and aftermath effects are addressed by [9,[90][91][92]. The transition to "Industry 4.0" is supported by several studies, to make SCs more interconnected to combat future disruptions [22,43,[93][94][95][96][97].…”
Section: Sc Sustainability and Viability During Disasters/outbreak Produced Ripple Effectsmentioning
confidence: 99%
“…For instance, El Baz, Laguir, and Stekelorum (2019) present one of the first literature reviews on logistics and supply chain management in Africa and identify a broad range of propositions for future research. Additional recent works provide new directions for research in the field of operations management, some of which are relevant to Africa (e.g., Lee & Tang, 2018;Samson, 2020;Samson & Kalchschmidt, 2019;Sodhi & Tang, 2021;Zhang et al, 2020). Instead of providing a research agenda, this Supplement presents an invitation to Africans and Africanists who work in the broader field of operations management and innovation to take part in the dialogue, undertake research to advance Africa in the 4IR, publish their work, and inspire or be inspired by others worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…These three phenomena have impacted the way firms manage their operations. Thus, the recent calls in the literature for new directions in research in the broad field of operations management (OM) are not surprising (e.g., Lee & Tang, 2018;Sodhi & Tang, 2021;Zhang, Wu, Tang, Feng, & Dai, 2020). Lee and Tang (2018) argue for broader OM research on socially and environmentally responsible value chains that includes challenges that are not widespread in developing economies, such as (1) contexts/constraints that are inherent to emerging and developing economies; (2) the objectives of companies that venture into developing markets to achieve the triple bottom line (economic, social, and environmental); and (3) the alignment of multiple stakeholders' interests (e.g., producers, consumers, shareholders, social enterprises, governments, and nongovernmental organizations).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation